Student Learning in South Asia : Challenges, Opportunities, and Policy Priorities - Dundar, Halil; Beteille, Tara; Riboud, Michelle; Deolalikar, Anil (Washington, DC: World Bank, 2014)
For the past decade, South Asian governments have been investing heavily to achieve the education millennium development goals (MDGs). The region has also made great progress in enrolling girls in both primary and secondary school. The rapid gains in enrollment have not been accompanied by commensurate improvements in learning levels, with the average level of skill acquisition in South Asia being low by both national and international standards. A major reason for this is that throughout the 2000s, most South Asian countries focused on: (a) achieving universal access to primary education, and (b) sustained investment in better-quality school inputs to improve the quality of primary and secondary education. This report covers education from primary through upper secondary school. Given its importance for school readiness, this report also reviews early childhood development even though that is outside formal education systems in the region. To examine what types of policies hold promise for improving student learning, it reviews data from large-scale national learning assessments and the findings of a small but increasing number of impact evaluations being conducted in the region. Finally, based on evidence from South Asia and other regions, it identifies strategic options and priorities to improve learning outcomes in South Asia. The findings make it clear that to be successful, policies to ensure lasting improvements in student learning outcomes need to be integrated into a larger agenda of inclusive economic growth and governance reform. This report makes an important contribution to ones understanding of the performance of education systems in South Asia and the causes and correlates of student learning outcomes. Further, drawing on successful initiatives both in the region and elsewhere in the world, it offers an insightful approach to setting priorities for enhancing the quality of school education despite growing competition for public resources.